APPROACHES TO THE AMPLE-FORM WORKS IN MUSIC SCHOOLS - Cătălina GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
Working on ample-form creations is a process consisting of certain phases, which a professor must go through with his/her students. In order to be able to approach this type of work, the student must be instructed by his/her professor to take the following steps: 1.Practice and study the scales and the crosshatches thoroughly, so that the left-hand and right-hand techniques are equally developed; 2.Become familiar with the studies that contain crosshatches from the concerto, which will be approached later. In addition to the previously mentioned steps, we emphasize the fact that studying smaller works is also very important. Prior to exercising the concerto, the professor must explain to the student what an ample form is and what the specifics of this form are, that is its phrasing mode and its method of interpreting hatches, accents, nuances, the melodic course and rhythm. To help the student study the work more easily and approach it correctly from an interpretative and stylistic point of view, the professor should present him/her with information regarding the composer’s biography, the style of the concerto and the period in which it was composed.